2021
DOI: 10.1245/s10434-021-10375-6
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Assessment of Quality of Life Following Molecular Testing for Indeterminate Thyroid Nodules

Abstract: Background Molecular testing can refine the risk of malignancy in cytologically indeterminate thyroid nodules and can reduce the need for diagnostic thyroidectomy. However, quality of life (QOL) in patients mananged with molecular testing is not well studied. Objective We aimed to assess the QOL of patients undergoing surveillance after a benign molecular test result, or thyroidectomy after a suspicious molecular test result. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…The second molecular approach, named gene-expression classifier (GEC) (Veracyte Afirma GSC), was designed to identify benign, rather than malignant, nodules, through the analysis of the expression level of 167 genes in the RNA extracted from FNA biopsies [ 43 , 44 ]. From both tests, a negative result effectively refines the risk of malignancy of AUS/FLUS and FN/SFN diagnostic categories to about 3–4%, comparable to that observed for a benign BSRTC diagnosis [ 45 , 46 ]. Thus, the evaluation and clinical management of thyroid nodules with indeterminate cytology (AUS/FLUS and FN/SFN) should comprise, besides cytology, clinical (i.e., personal or family history of thyroid cancer, lesion size, US features, and elastography) and possibly molecular information.…”
Section: Thyroid Nodulesmentioning
confidence: 92%
See 2 more Smart Citations
“…The second molecular approach, named gene-expression classifier (GEC) (Veracyte Afirma GSC), was designed to identify benign, rather than malignant, nodules, through the analysis of the expression level of 167 genes in the RNA extracted from FNA biopsies [ 43 , 44 ]. From both tests, a negative result effectively refines the risk of malignancy of AUS/FLUS and FN/SFN diagnostic categories to about 3–4%, comparable to that observed for a benign BSRTC diagnosis [ 45 , 46 ]. Thus, the evaluation and clinical management of thyroid nodules with indeterminate cytology (AUS/FLUS and FN/SFN) should comprise, besides cytology, clinical (i.e., personal or family history of thyroid cancer, lesion size, US features, and elastography) and possibly molecular information.…”
Section: Thyroid Nodulesmentioning
confidence: 92%
“…Thus, a considerable number of patients might undergo unnecessary thyroid surgical procedures [ 26 , 39 , 40 ]. In this context, the great advance in the comprehension of the molecular pathogenesis of thyroid cancer progression has led to the generation of new molecular approaches capable of ameliorating the diagnostic accuracy of FNAC alone, and to support therapeutic decisions [ 41 , 42 , 43 , 44 , 45 , 46 ]. In particular, two distinct molecular tests to evaluate FNA samples have entered clinical practice for the management of thyroid nodules [ 42 , 44 ].…”
Section: Thyroid Nodulesmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients under surveillance may experience some degree of cyclic psychological distress centering around their yearly follow-up visits, although evidence supporting that assumption is currently lacking and we have not observed it in the EfFECTS trial [ 26 ]. A recent study with a limited median 15-month follow-up found no evidence of such effects and showed sustained HRQoL in patients under surveillance following a negative molecular test [ 39 ]. We included the disutilities of both observation after HT and observation after a negative [ 18 F]FDG-PET/CT scan in our univariate sensitivity analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who underwent diagnostic surgery for a suspicious molecular test result, showed deteriorated goitre, depression and anxiety scores at the first assessment after molecular testing, all of which had improved eight months after surgery. Short-term postoperative HRQoL measurements were not available (23).…”
Section: Discussionmentioning
confidence: 99%